Enfranchisement regimes beyond de-territorialization and post-nationalism: definitions, implications, and public support for different electorates. Issue 7 (3rd October 2022) - Blatter, Joachim; Michel, Elie; Schmid, Samuel D.
ABSTRACT: This article starts from the premise that those who debate and study the expansion of demoi/electorates – from practitioners to empirical scholars and normative theorists – should consider more seriously that migrants are always immigrants and emigrants at the same time. Doing so implies, first, that states can regulate their electorates through four distinct "enfranchisement regimes" in times of transnational mobility: (1) national, (2) territorial, (3) generally inclusive, and (4) generally exclusive. Second, because the spread of dual/multiple citizenship is strongly intertwined with the expansion of the electorates beyond residency and/or nationality, various enfranchisement regimes have inherent consequences for the architecture of the international order and for political equality. Arguing that they have been largely overlooked, in this article we systematically tease out these consequences. We then apply our conceptual insights in a public opinion survey conducted among resident citizens across 26 European countries. We ask them about their preferred composition of the electorate, offering them all four regulatory options. Two results stand out. First, generally exclusive and generally inclusive regimes receive unexpectedly strong support. Second, support for different enfranchisement regimes varies strongly across European countries. We conclude by stressing how these insights are relevant to related normative and empirical discourses.